Trace metal sorption ability of insolubilized humic acids - Varrault, G.; Bermond, A. (Environmental Technology, 2002)
The objective of this work was to study the trace metal sorption ability of insolubilized Humic Acids (IHA) in comparison with regular Humic Acids (HA). IHA were prepared from HA by heating at 330degreesC for one hour under a nitrogen atmosphere. A solubility study was carried out at different pH values in NaNO3 (0.1 M) as a background electrolyte. It showed that IHA were insoluble until pH 10 whereas the solubility of HA increased with pH in one main step in the pH range 4-5 over which the soluble fraction of humic acids increased from 10% to 90%. We observed that trace metal sorption was dramatically influenced by these solubility properties. Indeed this study showed that above pH 5-6, HA and MA may have opposite effects in terms of trace metal sorption. Solubilization of HA made possible the formation of soluble metal-humic complexes, retaining metal in solution even for pH at which hydroxide can form. Under such pH conditions, which very numerous soils show, HA could be involved in the transport and uptake of trace metals in the plant-soil system. In terms of remediation, HA are not a suitable binding phase. On the contrary IHA were not solubilized at neutral and alkaline pH avoiding then the solubilization of sorbed trace metals. They appeared to be a suitable binding additive phase for future remediation trials.